A Continuous Illusion of Having a Sixth Finger. (August 2020) - Cadete, Denise; Longo, Matthew R.
Our body is central to our sense of self and personal identity, yet it can be manipulated in the laboratory in surprisingly easy ways. Several multisensory illusions have shown the flexibility of the mental representation of our bodies by inducing the illusion of owning an artificial body part or having a body part with altered features. Recently, new studies showed we can embody additional body parts such as a supernumerary finger. Newport et al. recently reported a novel six-finger illusion using conflicting visual and tactile signals induced with the mirror box to create the illusory perception of having a sixth finger for a brief moment. In this study, we aimed to replicate this result and to investigate whether the experience of embodiment of a sixth finger could be prolonged for an extended duration by applying continuous visual–tactile stimulation. Results showed that a continuous illusion of having a sixth finger can be clearly induced. This shows that the six-finger illusion does not reflect merely a momentary confusion due to conflicting multisensory signals but can reflect an enduring representation of a supernumerary finger.